10.9k views
4 votes
The equation f(x)=2x−9f(x)=2x−9 translated 6 units up is
g(x)=

1 Answer

7 votes

Start from
f(x) = 2x - 9

When you vertically translate the graph of a function, you are adding a constant to that equation, i.e. you're performing the transformation


f(x) \to f(x) + k

You translate the function
k units up if
k>0 and k units down if
k<0

So, in your case, you have to add 6 to the function:


f(x) = 2x - 9 \to g(x) = f(x) + 6 = 2x - 9 + 6 = 2x - 3

User Daniele Bernardini
by
6.2k points